Conservação pós-colheita de cebola em função da adubação potássica. - Fernandes, Bruno Caio Chaves (Universidade Federal Rural do Semi-Árido, 2017)
Higher post-harvest conservation is important when the onion is marketed, which presents large price changes in short time. The producer, based on the knowledge of the mass losses, will be able to achieve better price quotations and increase its profits, due to the volatility of the market. The essential role of potassium in numerous physiological and biochemical processes in the plant has been reported in relation to onion production and quality. An adequate content in the bulb is also important for the quality of storage. The objective of this work was to evaluate the effect of potassium fertilization on chemical characteristics and loss of mass during post-harvest storage of the cultivars "Ipa 11" and "Rio das Antas". The experimental design was a randomized block design, with four replications. The treatments were arranged in subdivided plots, the plots being represented by the potassium doses 0, 70, 140, 210 kg ha1, and the subplots the storage times, 0, 15, 30, 45 and 60 days, for each cultivar. We evaluated loss of mass, soluble solids, total soluble sugars, titratable acidity, pH, soluble solids/titratable acidity ratio and pungency. Potassium fertilization had a greater effect on the cultivar IPA 11, in which higher doses of K2O obtained an increase in pH, titratable acidity and sugars, as well a reduction of mass loss, pungency, soluble solids and SS/AT during the time of storage. For the cultivar Rio das Antas, no effect of K2O doses was observed for pH, acidity and SS / AT, the higher doses promoted an increase in soluble solids content, reduction in pungency and sugars, and a small difference in the percentage of mass loss, during storage time
Post-harvest conservation of onion due to potassium fertilization
Keywords: Allium cepa; Armazenamento; Nutrição; Allium cepa; Storage; Nutrition; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA